OFEVALUATION OFEVALUATION OF EVALUATION OFEVALUATION OF EVALUATION OF ROAD TRAFFIC IMPACT ON THE AQUIFERS OF ROAD TRAFFIC IMPACT ON THE AQUIFERS OFROAD TRAFFIC IMPACT ON THE AQUIFERS OFROAD TRAFFIC IMPACT ON THE AQUIFERS OF ROAD TRAFFIC IMPACT ON THE AQUIFERS OF ROAD TRAFFIC IMPACT ON THE AQUIFERS OF ROAD TRAFFIC IMPACT ON THE AQUIFERS OFROAD TRAFFIC IMPACT ON THE AQUIFERS OFROAD TRAFFIC IMPACT ON THE AQUIFERS OFROAD TRAFFIC IMPACT ON THE AQUIFERS OFROAD TRAFFIC IMPACT ON THE AQUIFERS OF ROAD TRAFFIC IMPACT ON THE AQUIFERS OFROAD TRAFFIC IMPACT ON THE AQUIFERS OF ROAD TRAFFIC IMPACT ON THE AQUIFERS OFROAD TRAFFIC IMPACT ON THE AQUIFERS OF ROAD TRAFFIC IMPACT ON THE AQUIFERS OF THE THE THE CROSSED AREAS. APPLICATION TO ROSSED AREAS. APPLICATION TOROSSED AREAS. APPLICATION TOROSSED AREAS. APPLICATION TO ROSSED AREAS. APPLICATION TO ROSSED AREAS. APPLICATION TOROSSED AREAS. APPLICATION TO ROSSED AREAS. APPLICATION TO ROSSED AREAS. APPLICATION TO ROSSED AREAS. APPLICATION TOROSSED AREAS. APPLICATION TO ROSSED AREAS. APPLICATION TOROSSED AREAS. APPLICATION TO ANNABA PLAIN ANNABA PLAIN ANNABA PLAINANNABA PLAINANNABA PLAIN CROSSED BY CROSSED BY CROSSED BYCROSSED BYCROSSED - S., Halimi (university of eloued جامعة الوادي, 2020)
In the Annaba plain, contamination of groundwater and road runoff by heavy metals was In the Annaba plain, contamination of groundwater and road runoff by heavy metals was In the Annaba plain, contamination of groundwater and road runoff by heavy metals was In the Annaba plain, contamination of groundwater and road runoff by heavy metals was In the Annaba plain, contamination of groundwater and road runoff by heavy metals was In the Annaba plain, contamination of groundwater and road runoff by heavy metals was In the Annaba plain, contamination of groundwater and road runoff by heavy metals was In the Annaba plain, contamination of groundwater and road runoff by heavy metals was In the Annaba plain, contamination of groundwater and road runoff by heavy metals was In the Annaba plain, contamination of groundwater and road runoff by heavy metals was In the Annaba plain, contamination of groundwater and road runoff by heavy metals was In the Annaba plain, contamination of groundwater and road runoff by heavy metals was In the Annaba plain, contamination of groundwater and road runoff by heavy metals was In the Annaba plain, contamination of groundwater and road runoff by heavy metals was In the Annaba plain, contamination of groundwater and road runoff by heavy metals was In the Annaba plain, contamination of groundwater and road runoff by heavy metals was In the Annaba plain, contamination of groundwater and road runoff by heavy metals was In the Annaba plain, contamination of groundwater and road runoff by heavy metals was In the Annaba plain, contamination of groundwater and road runoff by heavy metals was In the Annaba plain, contamination of groundwater and road runoff by heavy metals was In the Annaba plain, contamination of groundwater and road runoff by heavy metals was In the Annaba plain, contamination of groundwater and road runoff by heavy metals was In the Annaba plain, contamination of groundwater and road runoff by heavy metals was In the Annaba plain, contamination of groundwater and road runoff by heavy metals was In the Annaba plain, contamination of groundwater and road runoff by heavy metals was In the Annaba plain, contamination of groundwater and road runoff by heavy metals was In the Annaba plain, contamination of groundwater and road runoff by heavy metals was In the Annaba plain, contamination of groundwater and road runoff by heavy metals was In the Annaba plain, contamination of groundwater and road runoff by heavy metals was In the Annaba plain, contamination of groundwater and road runoff by heavy metals was In the Annaba plain, contamination of groundwater and road runoff by heavy metals was In the Annaba plain, contamination of groundwater and road runoff by heavy metals was studied studiedstudied throu gh combining the geochemical and hydrochimical approaches. For different gh combining the geochemical and hydrochimical approaches. For different gh combining the geochemical and hydrochimical approaches. For different gh combining the geochemical and hydrochimical approaches. For different gh combining the geochemical and hydrochimical approaches. For different gh combining the geochemical and hydrochimical approaches. For different gh combining the geochemical and hydrochimical approaches. For different gh combining the geochemical and hydrochimical approaches. For different gh combining the geochemical and hydrochimical approaches. For different gh combining the geochemical and hydrochimical approaches. For different gh combining the geochemical and hydrochimical approaches. For different gh combining the geochemical and hydrochimical approaches. For different gh combining the geochemical and hydrochimical approaches. For different gh combining the geochemical and hydrochimical approaches. For different gh combining the geochemical and hydrochimical approaches. For different gh combining the geochemical and hydrochimical approaches. For different gh combining the geochemical and hydrochimical approaches. For different gh combining the geochemical and hydrochimical approaches. For different gh combining the geochemical and hydrochimical approaches. For different gh combining the geochemical and hydrochimical approaches. For different gh combining the geochemical and hydrochimical approaches. For different gh combining the geochemical and hydrochimical approaches. For different gh combining the geochemical and hydrochimical approaches. For different gh combining the geochemical and hydrochimical approaches. For different gh combining the geochemical and hydrochimical approaches. For different gh combining the geochemical and hydrochimical approaches. For different gh combining the geochemical and hydrochimical approaches. For different gh combining the geochemical and hydrochimical approaches. For different gh combining the geochemical and hydrochimical approaches. For different gh combining the geochemical and hydrochimical approaches. For different gh combining the geochemical and hydrochimical approaches. For different gh combining the geochemical and hydrochimical approaches. For different gh combining the geochemical and hydrochimical approaches. For different gh combining the geochemical and hydrochimical approaches. For different metals, the mineral sources of contamination, as well geochemical processes metals, the mineral sources of contamination, as well geochemical processes metals, the mineral sources of contamination, as well geochemical processes metals, the mineral sources of contamination, as well geochemical processes metals, the mineral sources of contamination, as well geochemical processes metals, the mineral sources of contamination, as well geochemical processes metals, the mineral sources of contamination, as well geochemical processes metals, the mineral sources of contamination, as well geochemical processes metals, the mineral sources of contamination, as well geochemical processes metals, the mineral sources of contamination, as well geochemical processes metals, the mineral sources of contamination, as well geochemical processes metals, the mineral sources of contamination, as well geochemical processes metals, the mineral sources of contamination, as well geochemical processes metals, the mineral sources of contamination, as well geochemical processes metals, the mineral sources of contamination, as well geochemical processes metals, the mineral sources of contamination, as well geochemical processes metals, the mineral sources of contamination, as well geochemical processes metals, the mineral sources of contamination, as well geochemical processes metals, the mineral sources of contamination, as well geochemical processes metals, the mineral sources of contamination, as well geochemical processes metals, the mineral sources of contamination, as well geochemical processes metals, the mineral sources of contamination, as well geochemical processes metals, the mineral sources of contamination, as well geochemical processes metals, the mineral sources of contamination, as well geochemical processes metals, the mineral sources of contamination, as well geochemical processes metals, the mineral sources of contamination, as well geochemical processes metals, the mineral sources of contamination, as well geochemical processes metals, the mineral sources of contamination, as well geochemical processes metals, the mineral sources of contamination, as well geochemical processes metals, the mineral sources of contamination, as well geochemical processes metals, the mineral sources of contamination, as well geochemical processes metals, the mineral sources of contamination, as well geochemical processes metals, the mineral sources of contamination, as well geochemical processes metals, the mineral sources of contamination, as well geochemical processes metals, the mineral sources of contamination, as well geochemical processes metals, the mineral sources of contamination, as well geochemical processes metals, the mineral sources of contamination, as well geochemical processes weathering were established. The understanding of the geochemical mechanisms involv weathering were established. The understanding of the geochemical mechanisms involvweathering were established. The understanding of the geochemical mechanisms involv weathering were established. The understanding of the geochemical mechanisms involv weathering were established. The understanding of the geochemical mechanisms involv weathering were established. The understanding of the geochemical mechanisms involvweathering were established. The understanding of the geochemical mechanisms involvweathering were established. The understanding of the geochemical mechanisms involv weathering were established. The understanding of the geochemical mechanisms involv weathering were established. The understanding of the geochemical mechanisms involv weathering were established. The understanding of the geochemical mechanisms involv weathering were established. The understanding of the geochemical mechanisms involv weathering were established. The understanding of the geochemical mechanisms involv weathering were established. The understanding of the geochemical mechanisms involv weathering were established. The understanding of the geochemical mechanisms involv weathering were established. The understanding of the geochemical mechanisms involv weathering were established. The understanding of the geochemical mechanisms involv weathering were established. The understanding of the geochemical mechanisms involvweathering were established. The understanding of the geochemical mechanisms involvweathering were established. The understanding of the geochemical mechanisms involv weathering were established. The understanding of the geochemical mechanisms involvweathering were established. The understanding of the geochemical mechanisms involvweathering were established. The understanding of the geochemical mechanisms involv weathering were established. The understanding of the geochemical mechanisms involvweathering were established. The understanding of the geochemical mechanisms involvweathering were established. The understanding of the geochemical mechanisms involvweathering were established. The understanding of the geochemical mechanisms involvweathering were established. The understanding of the geochemical mechanisms involv weathering were established. The understanding of the geochemical mechanisms involv weathering were established. The understanding of the geochemical mechanisms involv ed anded and ed and the realized assessment allowed determining origins the realized assessment allowed determining origins the realized assessment allowed determining originsthe realized assessment allowed determining the origins the realized assessment allowed determining originsthe realized assessment allowed determining the originsthe realized assessment allowed determining the origins the realized assessment allowed determining originsthe realized assessment allowed determining the origins the realized assessment allowed determining originsthe realized assessment allowed determining the origins the realized assessment allowed determining originsthe realized assessment allowed determining the origins the realized assessment allowed determining originsthe realized assessment allowed determining the origins the realized assessment allowed determining origins the realized assessment allowed determining origins the realized assessment allowed determining origins the realized assessment allowed determining origins the realized assessment allowed determining origins the realized assessment allowed determining origins the realized assessment allowed determining origins the realized assessment allowed determining origins , the modes of the modes of the modes of transport transport (collective or collective or collective or collective or collective or collective or collective or collective or individual individual , heavy or light heavy or lightheavy or light heavy or light heavy or light heavy or light ) and control of metals in the plain. and control of metals in the plain. and control of metals in the plain. and control of metals in the plain. and control of metals in the plain. and control of metals in the plain. and control of metals in the plain. and control of metals in the plain. and control of metals in the plain. and control of metals in the plain. In this study, we examine the In this study, we examine the In this study, we examine the In this study, we examine the In this study, we examine the In this study, we examine the In this study, we examine the In this study, we examine the In this study, we examine the In this study, we examine the In this study, we examine the In this study, we examine the In this study, we examine the In this study, we examine the risks of road traffic on the quality groundwater and risks of road traffic on the quality groundwater and risks of road traffic on the quality groundwater and risks of road traffic on the quality groundwater and risks of road traffic on the quality groundwater and risks of road traffic on the quality groundwater and roadrisks of road traffic on the quality groundwater and roadrisks of road traffic on the quality groundwater and risks of road traffic on the quality groundwater and roadrisks of road traffic on the quality groundwater and risks of road traffic on the quality groundwater and risks of road traffic on the quality groundwater and roadrisks of road traffic on the quality groundwater and roadrisks of road traffic on the quality groundwater and risks of road traffic on the quality groundwater and risks of road traffic on the quality groundwater and risks of road traffic on the quality groundwater and risks of road traffic on the quality groundwater and risks of road traffic on the quality groundwater and risks of road traffic on the quality groundwater and roadrisks of road traffic on the quality groundwater and risks of road traffic on the quality groundwater and roadrisks of road traffic on the quality groundwater and roadrisks of road traffic on the quality groundwater and risks of road traffic on the quality groundwater and risks of road traffic on the quality groundwater and runof f in the Annaba plain crossed f in the Annaba plain crossed f in the Annaba plain crossed f in the Annaba plain crossed f in the Annaba plain crossed f in the Annaba plain crossed f in the Annaba plain crossed f in the Annaba plain crossed f in the Annaba plain crossed f in the Annaba plain crossed f in the Annaba plain crossed f in the Annaba plain crossed f in the Annaba plain crossed by three important communication by three important communication by three important communication by three important communication by three important communication by three important communication by three important communication by three important communication by three important communication by three important communication by three important communication by three important communication nationals nationals nationals nationals roads: roads: RN 44, 21 and 16RN 44, 21 and 16 RN 44, 21 and 16 RN 44, 21 and 16 RN 44, 21 and 16RN 44, 21 and 16 RN 44, 21 and 16 . The survey was carried . The survey was carried . The survey was carried . The survey was carried . The survey was carried . The survey was carried . The survey was carried . The survey was carried . The survey was carried . The survey was carried . The survey was carried . The survey was carried . The survey was carried out in June 2011, April 2012 and December 2013 covers the transport of heavy metals out in June 2011, April 2012 and December 2013 covers the transport of heavy metals out in June 2011, April 2012 and December 2013 covers the transport of heavy metals out in June 2011, April 2012 and December 2013 covers the transport of heavy metals out in June 2011, April 2012 and December 2013 covers the transport of heavy metals out in June 2011, April 2012 and December 2013 covers the transport of heavy metals out in June 2011, April 2012 and December 2013 covers the transport of heavy metals out in June 2011, April 2012 and December 2013 covers the transport of heavy metals out in June 2011, April 2012 and December 2013 covers the transport of heavy metals out in June 2011, April 2012 and December 2013 covers the transport of heavy metals out in June 2011, April 2012 and December 2013 covers the transport of heavy metals out in June 2011, April 2012 and December 2013 covers the transport of heavy metals out in June 2011, April 2012 and December 2013 covers the transport of heavy metals out in June 2011, April 2012 and December 2013 covers the transport of heavy metals out in June 2011, April 2012 and December 2013 covers the transport of heavy metals out in June 2011, April 2012 and December 2013 covers the transport of heavy metals out in June 2011, April 2012 and December 2013 covers the transport of heavy metals out in June 2011, April 2012 and December 2013 covers the transport of heavy metals out in June 2011, April 2012 and December 2013 covers the transport of heavy metals out in June 2011, April 2012 and December 2013 covers the transport of heavy metals out in June 2011, April 2012 and December 2013 covers the transport of heavy metals out in June 2011, April 2012 and December 2013 covers the transport of heavy metals out in June 2011, April 2012 and December 2013 covers the transport of heavy metals out in June 2011, April 2012 and December 2013 covers the transport of heavy metals out in June 2011, April 2012 and December 2013 covers the transport of heavy metals out in June 2011, April 2012 and December 2013 covers the transport of heavy metals out in June 2011, April 2012 and December 2013 covers the transport of heavy metals out in June 2011, April 2012 and December 2013 covers the transport of heavy metals out in June 2011, April 2012 and December 2013 covers the transport of heavy metals out in June 2011, April 2012 and December 2013 covers the transport of heavy metals out in June 2011, April 2012 and December 2013 covers the transport of heavy metals out in June 2011, April 2012 and December 2013 covers the transport of heavy metals out in June 2011, April 2012 and December 2013 covers the transport of heavy metals out in June 2011, April 2012 and December 2013 covers the transport of heavy metals out in June 2011, April 2012 and December 2013 covers the transport of heavy metals out in June 2011, April 2012 and December 2013 covers the transport of heavy metals from the road traffic in roadsides e from the road traffic in roadsides e from the road traffic in roadsides e from the road traffic in roadsides e from the road traffic in roadsides e from the road traffic in roadsides e from the road traffic in roadsides efrom the road traffic in roadsides e from the road traffic in roadsides efrom the road traffic in roadsides e from the road traffic in roadsides e from the road traffic in roadsides e from the road traffic in roadsides e from the road traffic in roadsides environm ent. The concentration of heavy metals Pbent. The concentration of heavy metals Pbent. The concentration of heavy metals Pb ent. The concentration of heavy metals Pb ent. The concentration of heavy metals Pbent. The concentration of heavy metals Pbent. The concentration of heavy metals Pb ent. The concentration of heavy metals Pbent. The concentration of heavy metals Pb ent. The concentration of heavy metals Pb ent. The concentration of heavy metals Pb ent. The concentration of heavy metals Pb ent. The concentration of heavy metals Pb ent. The concentration of heavy metals Pbent. The concentration of heavy metals Pb ent. The concentration of heavy metals Pb ent. The concentration of heavy metals Pb ent. The concentration of heavy metals Pbent. The concentration of heavy metals Pb2+ , Zn 2+ , Cu , Cu2+ and Feand Fe and Fe2+ in groundwater are respectively: 0.001 mg.l in groundwater are respectively: 0.001 mg.l in groundwater are respectively: 0.001 mg.l in groundwater are respectively: 0.001 mg.lin groundwater are respectively: 0.001 mg.lin groundwater are respectively: 0.001 mg.l in groundwater are respectively: 0.001 mg.l in groundwater are respectively: 0.001 mg.l in groundwater are respectively: 0.001 mg.lin groundwater are respectively: 0.001 mg.lin groundwater are respectively: 0.001 mg.l in groundwater are respectively: 0.001 mg.l in groundwater are respectively: 0.001 mg.l in groundwater are respectively: 0.001 mg.l -1, 0.13 mg.l -1, 0.11 mg.l , 0.11 mg.l -1 and and 1.055 mg.l -1, on average , on average , on average , on average .
artical
Keywords: Annaba plain, Emissions, heavy metals, pollution, road traffic. Annaba plain, Emissions, heavy metals, pollution, road traffic. Annaba plain, Emissions, heavy metals, pollution, road traffic. Annaba plain, Emissions, heavy metals, pollution, road traffic. Annaba plain, Emissions, heavy metals, pollution, road traffic. Annaba plain, Emissions, heavy metals, pollution, road traffic. Annaba plain, Emissions, heavy metals, pollution, road traffic. Annaba plain, Emissions, heavy metals, pollution, road traffic. Annaba plain, Emissions, heavy metals, pollution, road traffic. Annaba plain, Emissions, heavy metals, pollution, road traffic. Annaba plain, Emissions, heavy metals, pollution, road traffic. Annaba plain, Emissions, heavy metals, pollution, road traffic. Annaba plain, Emissions, heavy metals, pollution, road traffic. Annaba plain, Emissions, heavy metals, pollution, road traffic. Annaba plain, Emissions, heavy metals, pollution, road traffic. Annaba plain, Emissions, heavy metals, pollution, road traffic. Annaba plain, Emissions, heavy metals, pollution, road traffic. Annaba plain, Emissions, heavy metals, pollution, road traffic.